THE MOST ANCIENT IMPRINT OF THE "SEAL OF YASAWI" (Journal of history, 2024)
The article is devoted to determining the versions and history of the origin of the surviving seals associated with the name of Khoja Ahmed Yasawi. Along with scientific research on the seals of Khoja Ahmed Yasawi, the sources are the works of medieval chroniclers and Russian scientists, domestic and foreign researchers, as well as archival documents written about versions that have survived to this day. In the course of the study, written data on the seals of Khoja Ahmed Yasawi will be analyzed and clarified. In determining the object of research, methods of comparison, forecasting, analysis were used, aimed at disclosing the content of historical data and formulated facts. The scientific results of the article will complement our historical knowledge and present to the younger generation the religious and spiritual history of our people. In addition, these data can be used in the direction of the development of religious and spiritual tourism in our country. Key words: Khoja Ahmed Yasawi, seal, Sufism, written sources, historiography, Nasabnama, Islam.